Expert Consensus on Standard Terminology for Hair Transplantation (2024 Edition) - MIAO Yong; WU Wei; GONG Zhenyu; JIANG Wenjie; LI Yufei; HU Zhiqi; XIAN Hua; XIE Xiang; YANG Weiqi; ZHANG Dongyi; ZHANG Jufang; ZHANG Jiaxian; et al. (Xiehe Yixue Zazhi)
In order to promote the development of hair transplantation, particularly the establishment of standards, the Hair Transplantation Expert Group of Plastic and Aesthetic National Medical Quality Control Center invited experts in the field of hair transplantation across China and formed a draft of the Expert Consensus on Standard Terminology for Hair Transplantation based on the collation of relevant literature and monographs. By combining Delphi methodology and consensus meetings, the expert group conducted several rounds of consultations on issues such as follicular unit anatomy, harvesting, dissection, and implantation, ultimately presenting 54 terminologies. This consensus considers the original Chinese and English meanings as well as the professional characteristics of terms used in hair transplantation, highlights the unique features and advantages of hair transplantation, and preserves its essence while promoting innovation, with the hope of providing valuable reference for clinical researchers engaged in hair transplantation both domestically and internationally, and better facilitating the standardization and advancement of the field.